(untitled) (Journal of Social Sciences Review, 2025)
A deep ideological conflict that was latent but manifested in indirect conflicts in the areas strategically important to two major powers and an arms race marked the global political landscape in the era of what the world calls the "Cold War". Formulating and executing nuclear strategies was a significant factor in this conflict. The Soviet nuclear strategy, which evolved and altered with time according to the security threat its competitor posed, can be analyzed from the theoretical perspective of realism. This paper analyses the nature and evolution of the Soviet nuclear strategy by comparing the empirical manifestation of nuclear strategy in different periods with the tenets of this theoretical perspective. By scrutinizing the persistent and alternating themes in the evolution of Soviet nuclear strategy, this paper critically examines them with a lens that focuses on the survival and security of the state in an anarchical structure of international relations.